A colorless semi-aromatic polyimide derived from a sterically hindered bromine-substituted dianhydride exhibiting dual fluorescence and phosphorescence emission. (31st October 2018) - Kanosue, Kenta; Hirata, Shuzo; Vacha, Martin; Augulis, Ramūnas; Gulbinas, Vidmantas; Ishige, Ryohei; Ando, Shinji
Abstract : A colorless and thermally stable polyimide film exhibiting dual fluorescence and phosphorescence emission promising for solar spectral down-converters. Abstract : Colorless, transparent, and environmentally stable polymer films with large luminescence Stokes shift are in demand for down-conversion of solar UV radiation. To develop such a polymer film that exhibits phosphorescence at room-temperature with a large Stokes shift and excellent thermal stability, a semi-aromatic polyimide (DBrBP-PI) was newly synthesized using a biphenyltetracarboxylic dianhydride substituted with two bromine (Br) atoms. Thin films of DBrBP-PI were completely colorless because of effective suppression of the aggregation of the PI chains due to the steric effects of the Br-substituted dianhydride structure. The PI films exhibited bright green phosphorescence at 512 nm ( Φ = 0.02) with a very large Stokes shift of 12 215 cm −1 as well as prompt blue fluorescence at around 408 nm when excited at 315 nm at 298 K. The glass transition and the 5 wt% loss temperatures of DBrBP-PI were 325 °C and 427 °C, respectively. The phosphoresce intensity of the DBrBP-PI film was significantly enhanced under vacuum ( Φ = 0.22) and at low temperatures ( Φ = 0.76 at 77 K) owing to suppression of triplet state quenching by atmospheric oxygen and dumping of the molecular motions of the PI chains in the solid film. The suggested material design concept shows a way towards creation of stable and efficient down-converters for UV radiation.